Exogenous LIN28 Is Required for the Maintenance of Self-Renewal and Pluripotency in Presumptive Porcine-Induced Pluripotent Stem Cells - Chakritbudsabong, Warunya; Chaiwattanarungruengpaisan, Somjit; Sariya, Ladawan; Pamonsupornvichit, Sirikron; Ferreira, Joao N.; Sukho, Panithi; Gronsang, Dulyatad; Tharasanit, Theerawat; Dinnyes, Andras; Rungarunlert, Sasitorn (Frontiers in Cell and Developmental Biology, 2021)
Porcine species have been used in preclinical transplantation models for assessing the efficiency and safety of transplants before their application in human trials. Porcine-induced pluripotent stem cells (piPSCs) are traditionally established using four transcription factors (4TF): OCT4, SOX2, KLF4, and C-MYC. However, the inefficiencies in the reprogramming of piPSCs and the maintenance of their self-renewal and pluripotency remain challenges to be resolved. LIN28 was demonstrated to play a vital role in the induction of pluripotency in humans. To investigate whether this factor is similarly required by piPSCs, the effects of adding LIN28 to the 4TF induction method (5F approach) on the efficiency of piPSC reprogramming and maintenance of self-renewal and pluripotency were examined. Using a retroviral vector, porcine fetal fibroblasts were transfected with human OCT4, SOX2, KLF4, and C-MYC with or without LIN28. The colony morphology and chromosomal stability of these piPSC lines were examined and their pluripotency properties were characterized by investigating both their expression of pluripotency-associated genes and proteins and in vitro and in vivo differentiation capabilities. Alkaline phosphatase assay revealed the reprogramming efficiencies to be 0.33% and 0.17% for the 4TF and 5TF approaches, respectively, but the maintenance of self-renewal and pluripotency until passage 40 was 6.67% and 100%, respectively. Most of the 4TF-piPSC colonies were flat in shape, showed weak positivity for alkaline phosphatase, and expressed a significantly high level of SSEA-4 protein, except for one cell line (VSMUi001-A) whose properties were similar to those of the 5TF-piPSCs; that is, tightly packed and dome-like in shape, markedly positive for alkaline phosphatase, and expressing endogenous pluripotency genes (pOCT4, pSOX2, pNANOG, and pLIN28), significantly high levels of pluripotent proteins (OCT4, SOX2, NANOG, LIN28, and SSEA-1), and a significantly low level of SSEA-4 protein. VSMUi001-A and all 5F-piPSC lines formed embryoid bodies, underwent spontaneous cardiogenic differentiation with cardiac beating, expressed cardiomyocyte markers, and developed teratomas. In conclusion, in addition to the 4TF, LIN28 is required for the effective induction of piPSCs and the maintenance of their long-term self-renewal and pluripotency toward the development of all germ layers. These piPSCs have the potential applicability for veterinary science.